THE INFLUENCE OF GREEN ACCOUNTING AND CORPORATE SOCIAL RESPONSIBILITY ON THE PROFITABILITY OF MINING COMPANIES - Devi Ayu Putri; Novita Maretti Simangunsong (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2026)
Profitability is a crucial aspect that reflects the extent to which a company generates profits from its business activities. Profitability is the primary foundation that determines a company's long-term sustainability and competitiveness. Profitability not only reflects a company's ability to generate revenues greater than its costs but also serves as a key indicator of managerial effectiveness in efficiently managing resources. In practice, a company's profitability can increase or decrease, influenced by various factors, both internal, such as cost efficiency, and external, such as market conditions. This study aims to determine the effect of the implementation of Green Accounting (X1) and Corporate Social Responsibility (X2) on profitability (Y). The population used was all mining companies listed on the Indonesia Stock Exchange from 2020 to 2024. Based on the purposive sampling method, 20 companies were selected for the five research periods, resulting in a total sample of 100. The results of the partial t-test analysis showed that green accounting had no effect on profitability, and corporate social responsibility had a positive and significant effect on profitability. Meanwhile, the results of the F-test analysis (simultaneous) show that green accounting and corporate social responsibility together have a positive and significant effect on profitability in mining companies listed on the Indonesia Stock Exchange for the 2020-2024 period.